Screening for Excessive Alcohol Consumption in Emergency Departments: A Nationwide Assessment of Emergency Department Physicians. Issue 1 (12th January 2022) - Uong, Stephen; Tomedi, Laura E.; Gloppen, Kari M.; Stahre, Mandy; Hindman, Patrick; Goodson, Valerie N.; Crandall, Cameron; Sklar, David; Brewer, Robert D.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To assess current screening practices for excessive alcohol consumption, as well as perceived barriers, perceptions, and attitudes toward performing this screening among emergency department (ED) physicians. Design: A brief online assessment of screening practices for excessive drinking was disseminated electronically to a representative panel of ED physicians from November 2016 to January 2017. Descriptive statistics were calculated on the frequency of alcohol screening, factors affecting screening, and attitudes toward screening. Setting: An online assessment was sent to a national panel of ED physicians. Participants: A panel of ED physicians who volunteered to be part of the American College of Emergency Physicians Emergency Medicine Practice Research Network survey panel. Main Outcome Measure: The primary outcome measures were the percentage of respondents who reported screening for excessive alcohol consumption and the percentage of respondents using a validated excessive alcohol consumption screening tool. Results: Of the 347 ED physicians evaluated (38.6% response rate), approximately 16% reported "always/usually, " 70% "sometimes, " and 14% "never" screening adult patients (≥18 years) for excessive alcohol use. Less than 20% of the respondents who screened for excessive drinking used a recommended screening tool. Only 10.5% of all respondents (15.4% "always, " 9.5% "sometimes" screened) received an electronic health record (EHR) reminder to screen for excessive alcohol use. Key barriers to screening included limited time (66.2%) and treatment options for patients with drinking problems (43.1%). Conclusions: Only 1 in 6 ED physicians consistently screened their patients for excessive drinking. Increased use of EHR reminders and other systems interventions (eg, electronic screening and brief intervention) could help improve the delivery of screening and follow-up services for excessive drinkers in EDs.